Euler Approximations of Solutions of Abstract Equations and Their Applications in the Theory of Semigroups - Mishura, Yu. S.; Shevchenko, H. M. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
Using the Euler approximations of solutions of abstract differential equations, we obtain new approximation formulas for C 0-semigroups and evolution operators.